Fundos especiais e políticas públicas: Uma discuss\~ao sobre a fragilizaç\~ao do mecanismo de financiamento - Camillo de Moraes Bassi (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– It is discussed the weakening of special funds, as a mechanism for financing public policies. It operates on two fronts to support this fragilization. In the first one, innovations in the management of public resources are presented, making the funds expendable both to the linking of revenues and to the accumulation of balances (financial surplus). In the second, the idea of being funds (through the linkage of revenues) is disguised as a guarantee of resources for the purposes pursued. Exposure to the contingency contingency (arising from current tax rules), the constitution of a Contingency Reserve with own and/or linked revenues, in addition to the incidence of the DRU, underpin the aforementioned deconstruction. It is argued by way of conclusion that, on the financial flank, public policies are facing new challenges that (it is believed) have not yet been properly identified. How to face them, in turn, demands collegial decision, dialogical reason, that supplant the purposes of the investigation. Here we are content with this process of identification, which shortens spaces for confrontation.
Keywords: G23; H10; H81; 330; funds; public policies; financing